2022
DOI: 10.3389/fimmu.2022.951406
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress in innate immune cells - a significant contribution to non-alcoholic fatty liver disease

Abstract: Liver disease and its complications affect millions of people worldwide. NAFLD (non-alcoholic fatty liver disease) is the liver disease associated with metabolic dysfunction and consists of four stages: steatosis with or without mild inflammation (NAFLD), non-alcoholic steatohepatitis (NASH), fibrosis, and cirrhosis. With increased necroinflammation and progression of liver fibrosis, NAFLD may progress to cirrhosis or even hepatocellular carcinoma. Although the underlying mechanisms have not been clearly eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 141 publications
(155 reference statements)
1
7
0
Order By: Relevance
“…KC cells are the rst line of defense in the liver. When the HFHCC diet induces disorders of glucose and lipid metabolism, lipotoxicity caused by excessive accumulation of lipids in hepatocytes activates macrophages, leading to TNF-α, IL-6, and IL-1β, which further promotes liver steatosis, in ammation, and liver brosis [15]. In this study, In this study, immunohistochemical results showed that the HFHFF diet induced the activation of KCs.…”
Section: Discussionsupporting
confidence: 50%
“…KC cells are the rst line of defense in the liver. When the HFHCC diet induces disorders of glucose and lipid metabolism, lipotoxicity caused by excessive accumulation of lipids in hepatocytes activates macrophages, leading to TNF-α, IL-6, and IL-1β, which further promotes liver steatosis, in ammation, and liver brosis [15]. In this study, In this study, immunohistochemical results showed that the HFHFF diet induced the activation of KCs.…”
Section: Discussionsupporting
confidence: 50%
“…The latest study indicated that ER stress in innate immune cells contributes to NASH. For example, ATF6, by mediating a proinflammatory synergy between ER stress and TLR activation, is involved in the development of liver injury [ 35 ]. XBP1-mediated ER stress promoted steatohepatitis via NLRP3 inflammatory vesicle-mediated M1-type polarization [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This condition leads to the activation of transcription factors sensitive to oxidative stress, such as NF- κB. These, in turn, trigger Kupffer cells to produce pro-inflammatory mediators and further promote NAFLD progression [ 109 ].…”
Section: Pathogenesismentioning
confidence: 99%